Avoidance of heat and attraction to optogenetically induced sugar sensation as operant behavior in adult Drosophila - Nuwal, Nidhi; Stock, Patrick; Hiemeyer, Jochen; Schmid, Benjamin; Fiala, Andre; Buchner, Erich (Journal of Neurogenetics, 2012)
Animals have to perform adequate behavioral actions dependent on internal states and environmental situations, and adjust their behavior according to positive or negative consequences. The fruit fly Drosophila melanogaster represents a key model organism for the investigation of neuronal mechanisms underlying adaptive behavior. The authors are using a behavioral paradigm in which fruit flies attached to a manipulator can walk on a Styrofoam ball whose movements are recorded such that intended left or right turns of the flies can be registered and used to operantly control heat stimuli or optogenetic activation of distinct subsets of neurons. As proof of principle, the authors find that flies in this situation avoid heat stimuli but prefer optogenetic self-stimulation of sugar receptors. Using this setup it now should be possible to study the neuronal network underlying positive and negative value assessment of adult Drosophila in an operant setting. © 2012 Informa Healthcare USA, Inc.
Created from Fastlane, Scopus look-up
Keywords: Channelrhodopsin transgene; Gr5a-Gal4; Heat avoidance; Neuronal self-stimulation; Operant behavior; Sugar receptors; Walking ball apparatus